A pocket guide for student midwives - McKay-Moffat, Stella (Wiley-Blackwell, 2010)
"Written by two experienced midwives and lecturers, this new and updated edition of A Pocket Guide for Student Midwives is a must-read for both degree and diploma student midwives, as well as previously registered midwives. Focusing first on the language of midwifery, the book then goes on to explore common conditions, procedures, emergency situations and supporting information. Each topic may include further factors that involve recognition, prevention, and actions to take in an emergency situation that may be in the form of flow/action charts. This new edition has been updated to include the latest clinical guidelines, NMC directives and legislation.--Provided by publisher.